Social Psychological Characteristics of National Values in Patriotic Spirit Education of Adolescents (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article describes the role and importance of social institutions in forming the culture of information consumption of teenagers, protecting them from foreign ideas, and educating them in the spirit of patriotism. Pedagogical-psychological features of educating young people in the spirit of spirituality, education and patriotism, issues of organizing education and training based on the psychological approach to the formation of patriotic qualities are also mentioned.